(untitled) (Research, Society and Development, 2021)
Objective: to describe evidence related to maternal complications during pregnancy due to SARS-COV-2 infection. Method: The search was conducted in Medline databases via Pubmed, Cochrane and Embase via Elsevier, whose search was carried out between March and April 2021. The descriptors used were indexed in the Medical Subject Headings (MeSH) system and in Emtree, namely: Pregnancy Complications, Infectious, COVID-19, SARS-CoV-2, pregnancy complication and coronavirus disease 2019. Articles published in Portuguese, English or Spanish, published between 2019-2021 and full articles with open access via Portal de Periódicos Capes, were included. Duplicate articles, articles focused on other themes, case reports, letter to the editor and review studies were excluded. Initially, 2,809 articles were obtained, being selected according to the following steps: identification, screening and eligibility. 18 articles were included for the synthesis of the final sample. Results: The main complications were spontaneous abortions, thrombocytpnea, perinatal deaths, premature rupture of membranes, premature birth and intrauterine fetal death. Most women were admitted to the ICU and experienced postpartum hemorrhage. There was an increase in emergency cesarean sections, and some suffered from Post Traumatic Stress Disorder, postpartum depression and post-abortion depression. Conclusion: Maternal complications were identified due to contamination by SARS-COV-2.